Role of melatonin in treatment of nonalcoholic steatohepatitis in rats induced by high fat diet - Kuzu, N.; Bahcecioglu, I. H.; Metin, K.; Ozercan, I. H.; Tuzcu, M.; Yalniz, M.; Şahin, Kazım (Elsevier Science Bv, 2007)
[Abstract Not Available]
42th Annual Meeting of the European-Association-for-the-Study-of-the-Liver -- APR 11-15, 2007 -- Barcelona, SPAIN